Lived Experiences of Nurse Leaders in Upholding Ethical Standards in Healthcare Settings - Torres-Jumamil, Feelin; Espina, , Edzen; Prado, Nenita (International Journal of Sustainability and Advanced Integrated Research, 2026)
In the dynamic field of nursing leadership, ethical decision-making remains a critical factor influencing patient care, staff welfare, and organizational outcomes. This study investigated how nurse leaders uphold ethical standards in their professional responsibilities, exploring the processes and behaviors that exemplify ethical leadership. The main purpose of the study was to identify specific situations requiring ethical judgment, understand the strategies employed by nurse leaders, and analyze how internal moral convictions align with professional standards to guide ethical actions. A qualitative research design was employed, and participated among nurse leaders in two (2) chosen public hospitals in the Province of Bukidnon in a qualitative study using NVivo theme analysis. Data were analyzed to extract patterns, insights, and experiences related to ethical decision-making. The relevance of this dissertation was further anchored in the national commitment to the United Nations Sustainable Development Goals, particularly Goal 3 (Good Health and Well-being), which emphasized strengthening the health workforce and promoting safe, effective, and equitable health care systems. Results revealed that ethical leadership emerges from a combination of conscience-guided reflection, resilience-building, and responsive action. Nurse leaders consistently displayed harmony between personal values, professional ethical codes, and leadership behaviors, which generated trust, accountability, and healthy organizational culture. The study concludes that ethical leadership is not an inherent trait but a continuously developed practice. Organizations that support reflective and principled leadership can enhance staff performance, patient safety, and overall institutional integrity.